MHD Casson Fluid Flow through a Parallel Plate - Afikuzzaman, Md.; Mahmud Alam, Md. (Science & Technology Asia, 2016)
Free convection and mass transfer Casson fluid flow through a parallel plate with uniform magnetic field is investigated. The uniform magnetic field is applied perpendicular to the plates and the fluid motion is subjected to a uniform suction and injection. The upper plate is moving and the lower plate is stationary. The momentum, energy and concentration equations have been solved by explicit finite difference method. The stability conditions and convergence analysis of the explicit finite difference scheme are established for finding the restriction of the values of various parameters to obtain converse solutions. The influence of various interesting parameters on the flow has been analyzed and discussed through graph in details. The values of Shear Stress, Nusselt number and Sherwood number for both moving and stationary plates for different physical parameters are also discussed in the graphical form.